(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The presented research deals with the emergence of e-government, its objectives, foundations, and the most prominent of them, In addition to the application of electronic government in Syria and the factors affecting its implementation and requirements, As well as the expected achievements of employing e-government in administrative reform. Accordingly, the main objective of the research is to identify the role of electronic government in achieving administrative reform, Knowledge of the options offered by e-government and the policy of developing these options in the face of regulatory challenges. Where the descriptive analytical approach was used to describe e-government and analyze the factors affecting its implementation and the expected achievements of its employment in administrative reform. The research reached a set of results, the most important of which are: E-government represents a turning point for the transition towards electronic public services, That is, the transition from direct contact of citizens with the public administration to virtual digital communication through electronic networks, And relying on information and communication technology to catch up with development and overcome problems and obstacles that limit the process of administrative reform, Considering it as an entry point through which to increase the efficiency of government organizations and improve their performance.